On the importance of very long‐term water quality records. (11th November 2013) - Burt, T.P.; Howden, N.J.K.; Worrall, F.
<x xml:space="preserve">Abstract</x> This overview is concerned with the value of long‐term records of water quality in river basin management. In a world where change rather than stasis is increasingly the norm, monitoring is an essential way to discover whether there are significant undesirable changes taking place in the natural environment. The regular collection and processing of information involves systematic and purposeful observation, a deliberate plan of action in which the data have considerable value given the knowledge of their context in time and space. Long‐term data reveal important patterns, which allow trends, cycles, and rare events to be identified. This is particularly important for complex systems where signals may be subtle and slow to emerge. Moreover, very long data sets are essential to test hypotheses undreamt of at the time the measurements were started. This overview includes long time series from UK rivers showing how water quality has changed over time—and continues to change. An important conclusion is the long time frame of system recovery, well beyond the normal lifetime of individual governments. At a time of increasing hydroclimatic variability, long time series of water quality observations remain critically important; continuity of observations is critical at key benchmark sites. WIREs Water 2014, 1:41–48. doi: 10.1002/wat2.1001 Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.